Integrating Health Drug Making with Information Technology Outsourcing in Thailand: Role of Outsourcing Capabilities on its Success - Smuntavekin, Sudpranorm; Chaopreecha, Oranuch; Lapwongwatana, Punyarat (International Journal of Psychosocial Rehabilitation, 2020)
The role of information technology is increasing day by day with the practice of hiring resources outside the organization. It is well known that the companies outsource the material as well as capabilities to make an effective and efficient business process. The given study has a primary aim is to highlight the impact of knowledge integration capabilities, management capabilities and IT capabilities on IT outsourcing success of the drug making industry in Thailand with the help of mediating the role of delivery of IT service. Additionally, for this purpose the data has been collected from male and female respondents, out of 52% were male and 47% were female. The data has been collected through a survey questionnaire with the help of a five-point Likert scale. Under the analysis, multiple techniques are used to examine the hypothesis of acceptance and rejection. At the same time, the skewness analysis is done to measure the coefficient of the scale. The results and tables have indicated that the IT capabilities and management capabilities both have a positive effect on outsourcing success of the companies while the integration capability has an insignificant impact on outsourcing success. Furthermore, the results have indicated that the delivery of IT service also has an emerging and positive mediating role.